CORRECT AND CAREFUL AS ONE OF THE REQUIREMENTS OF AN MUFASSIR - rika summalia (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2023)
The classical period (650M-1250M) was the peak period of the glory of Muslims. This period is divided into periods of expansion, integration and the peak of progress (650-1000 AD). Under the leadership of the caliphs, Islam experienced a very broad expansion of influence, towards the West through North Africa Islam reached Spain and towards the East through Persia, Islam reached India. This period was also marked by the development of science in the fields of religion and culture, the field of law, theology, Sufism, philosophy and science. The disintegration phase (1000-1250 AD) was marked by divisions and political setbacks of Muslims until it culminated in the taking of Baghdad by Hulagu's army in 1258 AD. The history of determining the conditions for mufassir cannot be separated from the history of the codification of Ulum Al-Qur'an, along with the expansion of areas influenced by Islam. In interpreting the Qur'an, of course, there are several conditions that must be fulfilled by a mufassir, some of which are physical and psychological, as well as those that are diniyyah (religious) and especially academic requirements. These conditions are intended so that the mufassir can produce correct interpretations and avoid mistakes and the products of his interpretation can be accepted. Non-Muslims whose interpretation is unacceptable because they are afraid it will cause confusion or distortion of Islamic religious teachings through their interpretation. Then psychologically, a mufassir must also have ethics in interpreting the Qur'an. In interpreting the Qur'an, of course, there are several conditions that must be fulfilled by a mufassir, some of which are physical and psychological, as well as those that are diniyyah (religious) and especially academic requirements. These conditions are intended so that the mufassir can produce correct interpretations and avoid mistakes and the products of his interpretation can be accepted. Non-Muslims whose interpretation is unacceptable because they are afraid it will cause confusion or distortion of Islamic religious teachings through their interpretation. Then psychologically, a mufassir must also have ethics in interpreting the Qur'an. In interpreting the Qur'an, of course, there are several conditions that must be fulfilled by a mufassir, some of which are physical and psychological, as well as those that are diniyyah (religious) and especially academic requirements. These conditions are intended so that the mufassir can produce correct interpretations and avoid mistakes and the products of his interpretation can be accepted. Non-Muslims whose interpretation is unacceptable because they are afraid it will cause confusion or distortion of Islamic religious teachings through their interpretation. Then psychologically, a mufassir must also have ethics in interpreting the Qur'an. These conditions are intended so that the mufassir can produce correct interpretations and avoid mistakes and the products of his interpretation can be accepted. Non-Muslims whose interpretation is unacceptable because they are afraid it will cause confusion or distortion of Islamic religious teachings through their interpretation. Then psychologically, a mufassir must also have ethics in interpreting the Qur'an. These conditions are intended so that the mufassir can produce correct interpretations and avoid mistakes and the products of his interpretation can be accepted. Non-Muslims whose interpretation is unacceptable because they are afraid it will cause confusion or distortion of Islamic religious teachings through their interpretation. Then psychologically, a mufassir must also have ethics in interpreting the Qur'an.